Avanzada Nacional: La derecha a la derecha de Pinochet - José Díaz Nieva (Centre de Recherches sur les Mondes Américains, 2016)
Avanzada Nacional was a political organization established in Chile at 1983 and which carried out its activities until 1991. Many of its members ended up joining the Unión de Centro Centro – Progresista. It was one of the many right-wing groups that supported the military government; but while most of these adapted to the new times that were seen to be coming after the plebiscite of 1988, Avanzada Nacional continued to be intransigent, maintaining – even – the necessity of nominating General Pinochet as a candidate in the 1989 presidential elections, despite the fact that he had decided to take refuge in the office of Commander-in-Chief of the Army and to leave that post to one of his civilian collaborators.